Viral kinetics of SARS-CoV-2 over the preclinical, clinical, and postclinical period. (January 2021) - Jang, Sukbin; Rhee, Ji-Young; Wi, Yu Mi; Jung, Bo Kyeung
Graphical abstract: Highlights: SARS-CoV-2 has a high viral load from 5 days before symptoms onset to 10 days after symptoms onset. rRT-PCR results are converted to negative approximately 3 weeks after the onset of symptoms. Ct values ​​for 6 weeks or longer were repeated negative and positive. It is necessary to consider the expansion of the scope of epidemiological investigations. Consider the release of isolation 10 days after symptom onset in limited resource situations. Abstract: Background: It is necessary to know the viral kinetics and conduct epidemiological investigations of confirmers to prevent the spread of the new infectious disease COVID-19 to the community. To date, no study has been published on viral kinetics during the preclinical and clinical periods of SARS-CoV-2. Methods: A confirmed case was defined as a patient with positive results by real-time reverse transcription polymerase chain reaction (RT-PCR) assay for SARS-CoV-2. Both specimen types were collected over the whole clinical course in all patients. Asymptomatic patients who had been screened for COVID-19 due to a strong epidemiological link were also enrolled. The study population included 54 hospitalized patients with confirmed COVID-19. Results: COVID-19 shows a very high viral load on the day of symptom development, which then decreases overall. Rapid viral proliferation was observed 0–5 days before symptoms developed. Cycle threshold (Ct) value was the lowest in the clinical course from 5 days before symptoms to 10 days after symptoms occurred (Ct < 30). The rRT-PCR results were negative approximately 3 weeks after the onset of symptoms. However, there was a continuous pattern that was negative and positive for up to 6 weeks and more. Conclusion: Considering the characteristic that COVID-19 has a high viral load before symptoms appear, it is necessary to consider to expand the scope of epidemiological investigations. As there is a very low possibility of transmission after 10 days of symptom occurrence, it may be considered to release isolation after 10 days of symptom occurrence in limited resource situations. This study allows for the planning of epidemiological investigations, patient's ward supply, and follow-up of patients through sequential changes in viral loads over the entire clinical course. In addition, it is possible to estimate the clinical time at which the patient is present.